Anticorrosive efficiency of alkyd resin-based coatings containing Mg–Zn–Fe mixed oxide-based pigments - Kalendová, Andréa; Halecká, Elena; Nechvílová, Kateřina; Kohl, Miroslav (My University, 2017)
Mixed oxide-based pigments Mg–Zn–Fe with different particle morphologies were prepared by high-temperature solid phase reactions. The core shell pigments containing ferric oxide and non-isometric particles of layered silicates were also prepared. The pigments were tested in paints, the pigment volume concentrations in the modifi ed alkyd resin based binder being 5%, 10%, and 15%. The paint properties were examined by accelerated corrosion tests and by physico-mechanical tests. The effect of the pigment particle morphology on the surface hardness of the paint fi lms was also studied. The influence of pigment volume concentration on the coating properties, and the optimum concentrations providing the most efficient anticorrosive protection were processed. A higher anticorrosion efficiency was observed for the paints with pigments possessing the lamellar particle shape.
Antikorozní účinnost nátěrových hmot na bázi modifikované alkydové pryskyřice s obsahem směsných oxidů Mg–Zn–Fe
Keywords: alkyd resin; paint; pigment; alkydová pryskyřice; nátěr; pigment